THE IMPLEMENTATION OF REPLACEMENT PERFORMANCE ROLE-PLAY IN TEACHING SPEAKING TO THE ELEVENTH GRADE STUDENTS OF MAN 2 BOJONEGORO (RETAIN, 2014)
THE IMPLEMENTATION OF REPLACEMENT PERFORMANCE ROLE-PLAY IN TEACHING SPEAKING TO THE ELEVENTH GRADE STUDENTS OF MAN 2 BOJONEGORO JOURNAL BY DINA ARFIANAH NIM. 102084053 ADVISOR RIRIN PUSPARINI, S.Pd., M.Pd. NIP. 19760521 200312 2 001 SURABAYA STATE UNIVERSITY FACULTY OF LANGUAGE AND ARTS ENGLISH EDUCATION DEPARTMENT ENGLISH STUDY PROGRAM 2014 THE IMPLEMENTATION OF REPLACEMENT PERFORMANCE ROLE-PLAY IN TEACHING SPEAKING TO THE ELEVENTH GRADE STUDENTS OF MAN 2 BOJONEGORO Dina Arfianah English Study Program FBS Surabaya State University dinaarfianah@gmail.com Ririn Pusparini, S.Pd., M.Pd. Lecturer of English Study Program FBS Surabaya State University rrn.puspa@gmail.com ABSTRACT Speaking is one skill that should be mastered by the language learners. In speaking class, the teacher should give the students a lot opportunity to practice the target language by speaking. In fact, most students are afraid when the teacher asked them to practice their speaking. In order to make the students have a lot oppurtunity to speak English, the researcher suggested the English teacher to use a technique called Replacement Performance Role Play. This study investigated how the implementation of Replacement Performance Role Play in teaching speaking in lights with the theories of Replacement Performance Role Play.The researcher conducted research to answer these following questions: How is the implementation of Replacement Performance Role Play in teaching speaking? How does the students’ response toward the implementation of Replacement Performance Role Play?. This study used descriptive qualitative research as research design. The data were taken from observation sheet, questionnaire and interview. The data were analyzed qualitatively. The result of this research was the implementation of in teaching speaking was good. The teacher implemented the technique appropriate with the theoris of Replacement Performance Role Play by using three phases speaking activity. Moreover, most of the students were participated a lot in each meeting because every student had same opportunities to develop their idea, expressing their idea and practicing their speaking skill. Besides, the students gave positive response toward the implementation of Replacement Performance Role Play. They can learn English easily and enjoyable. Key word : Replacement performance, role play and speaking. ABSTRAK Speaking adalah salah satu kemampuan yang harus dikuasai oleh siswa yang sedang belajar bahasa. Dalam menggajar speaking, guru harus memberikan kesempatan yang sebanyak-banyaknya kepada siwa untuk mempraktikkan bahasa yang mereka pelajari. Kenyataanya, banyak siswa merasa takut untuk berbicara bahasa inggris. Untuk membuat siswa lebih aktif berpartisipasi, peneliti menyarankan untuk menggunakan Replacement Performance Role Play. Penelitian ini menginvestigasi bagaimana penerapan Replacement Performance Role Play dalam mengajar speaking berkaitan dengan teori Replacement Performance Role Play. Peneliti melakukan penelitian untuk menjawab pertanyan berikut in: Bagaimana penerapan Replacement Performance Role Play dalam mengajar speaking? Bagaimana respon siswa terhadan diterapkannya Replacement Performance Role Play ? Penelitian ini menggunakan metode deskriptif kualitatif. Data penelitian diiambil dari lembar observasi, kuesioner dan wawancara. Selanjutnya, data tersebut di jelaskan secara deskriptif. Hasil dari penelitian ini adalah, penerapan Replacement Performance Role Play dalam mengajar speaking sangat bagus. Guru menerapkan teknik tiga tahap speaking yang sesuai teori Replacement Performance Role Play. Apalagi banyak siswa yang berpartisipasi pada tiap-tiap pertemuan karena setiap siswa mempunyai kesempatan yang sama untuk mengembangkan ide mereka, mengungkapkan ide mereka dan mempraktikkan kemampuan speaking mereka. Di samping itu, siswa memberikan respon yang bagus terhadap penerapan Replacement Performance Role Play. Mereka dapat belajar bahasa inggris dengan mudah dan menyenangkan. Key word : Replacement performance, role play and speaking. INTRODUCTION In learning English, there are four skills that should be mastered by students and one of them is speaking. According to Lindsay and Knight (2006 : 57) speaking is a productive skill that involves putting a message together, communicating the message, and interacting with other people. Mastering speaking skill is needed when the students want to communicate well. Moreover, people would like to use the language orally rather than written to communicate with others in daily life. For example, when the teachers want to communicate, ask for something or give explanation to the students, they usually speak up. An English teacher should be able to teach speaking effectively and in appropriate way. Nunan (2003) emphasized that speaking is the most important aspect of learning a second or foreign language and success measured in terms of the acquisition in language. This means that having good qualification in speaking ability is very important. One way that can be used by teacher to develop students speaking ability is by giving students a lot of opportunities to practice the language because the goal of speaking can be reached if all of students participate in speaking class. Nunan (2003) suggested that in speaking classroom, learners should be given the maximum number of opportunities possible to practice the target language in meaningful contexts and situation. The more they practice the target language that they learn, the easier they can acquire the language. In fact, most senior high school students feel afraid when their teacher asks them to practice their speaking. They often feel confused and prefer not to follow the lesson well or they prefer to keep silent. There are some factors that influence the students in participating in speaking class, such as: the student is afraid of making mistakes, the topic is not interesting and the classroom atmosphere is not encouraging. Moreover, teaching English in Indonesia is known as teaching English as a Foreign Language or EFL. Teaching speaking in EFL class is difficult because students lack of opportunity to speak. Brown (2001:117) emphasized that “EFL context is clearly a greater challenge for students and teachers”. The teacher needs to maximize a practice activity in class and makes the student to use the language as much as possible. Therefore, the language that delivered by the teacher in every meeting takes an important impact to the students. It is important to the teacher to provide an effective, enjoyable and interesting material. Teacher needs to prepare good strategies in order to make the speaking lesson run well. An effective speaking lesson can be reached when the students have a lot of opportunities to speak. In communicative classroom; teacher should provide materials that enable the learners to communicate with one another in order to develop their speaking skills. There are various methods that can be used by the teacher to create an effective speaking class. One of them is Communicative Language Teaching (CLT). This approach was focus on the communication that the students usually use in their life. Norland and Pruett-Said (2006: 31) pointed out that CLT is viewed as an approach to teaching that focus on fluency and the ability to communicate in a variety of setting and in a variety of way. The focus on CLT is on communication in authentic situations. The strength of this method is that it creates a learning environment that the student can use the target language in real life-situation. The application of this method is role play. Role play enables the student to practice the target language they have acquired. Harmer (2007 : 127) mentioned that role play has some advantages, such as: getting the students to speak in class, improving communicative competence and fluency, promoting cooperative learning and providing practice for real-life experience. Besides, role play is fun and motivating activity for student because it allows them to express themselves. Replacement performance role play is one kind of role play activity. Snarski (2007: 3) points out that replacement performance role play can make the students engaged naturally. It means that the participation of students in speaking will increase because students are practiced the target language naturally or unconsciously. It also has some benefits, such as making whole class participation, promoting pragmatic competence and helping develop critical thinking skills. In implementing Replacement Performance role play. The teacher used three phases speaking activity. a) Pre-Speaking Activity - The teacher asks the students to mention some examples of the expression that they will study and gives more examples. - The teacher explains the material and gives the example of some dialogues. Then, she/he practices the dialogues with the students. - Teacher plays a short scene; it can be a form of video. The students should pay attention to the story line and message in the scene. The teacher might play the scene twice or three times to make the student grasp the scene better b) Whilst-Speaking Activity - Teacher asks some questions to the students about the scene in the video they just viewed. Then, they discussed about the story of the video. - They teacher asks the students to find the expression that they are studying from the video. - Teacher divided the students into group consists of four or five students. - The teacher gives task to the students that are they have to make their own dialogue with the same story as the video. They might use their own words. - The teacher lets the students to discuss the task with their group and rewrites the dialogue for a Replacement Performance. - The teacher monitors the students and makes sure that all of students have participated in speaking. - The students practice their dialogue within their group. - The students perform the Replacement Performance in front of the class. c) Post-Speaking Activity - The teacher gives feedback to the students’ performance and asks the audience student to give comments too. In this study, the researcher found previous study which relate to this study. Based on Wijayanti (2010), the use of role play make the students can improve their ability of speaking. This previous study was different from the researcher study because the subject of the previous study was junior high school students and she used classic role play as a technique. Based on the explanation above, the research conducted to investigate How Replacement Performance Role Play is implemented in teaching speaking for eleventh grade students of senior high school at MAN 2 Bojonegoro and how the students’ response toward the implementation of How Replacement Performance Role Play. METHOD The research design used by the researchers is descriptive qualitative research. According to Ary (2010: 421), if the research is concerned with condition and relationship that exist; practice that prevail; beliefs, point of view, or attitude; or trends that are developing, the study is descriptive. In this research, the researcher took a part as an observer who observed activity of teacher and students during teaching learning process. The teaching learning process was conducted by the English teacher himself. The subjects of this study were the eleventh grade students of MAN 2 Bojonegoro and the English teacher. The researcher conducted the observation in XI Natural Science 3 Skill class which consists of 35 students, 17 male students and 18 female students. The data of this study derived from the result of three times observations which are obtained through observation checklist in three meetings and result of questionnaire and interview which was conducted at third meeting after the observation was over. First, the observation checklist was used to obtain detail information about the process of teaching learning process in speaking by using replacement performance role play. It consisted of several points which are identified the material, the technique and the activities of teacher and students in three phase speaking activities. Second, the questionnaire consists of ten questions in the form of multiple choices. There are two indicators being measured and elaborated in the questionnaire, they are the student’s opinion about speaking and the student’s opinion about the implemented of replacement performance role play. Last, the researcher also conducted little interview to the students in order to strengthen the result of questionnaire. The researcher used semi structured interview, which was the question are structured (almost same with questions in questionnaire) but the researcher may modify the questions during the interview process. In analyzing the data, the researcher used descriptive way. The result of observation checklist had been analyzed descriptively according to the fact and the researcher interpretation. Besides, the data from questionnaire and interview explained or concluded in an essay. RESULT AND DISCUSSION The Implementation of Replacement Performance Role Play in Teaching Speaking The observation was done on December 2nd 2013, May 3rd 2014 and May 5th 2014. It was held to gain the information about the implementation of Replacement Performance Role Play in teaching speaking for eleventh grade of MAN 2 Bojonegoro. The result of the observation was taken from observation checklist. There were three major concerns that observed by the researcher, these are: The material, the technique and teaching learning process. The first was the material. The teacher used the material that relevant with the objective of the study in each meeting. He chose the material that enabled students to have a lot opportunity to speak English more and to develop their idea in speaking. As suggested by Murray and Christison (2011: 91) that the teacher not to use material simply because it is available, but because it really serves the teaching purpose. The Materials were also in line with the students’ level. It was neither too difficult nor too easy for the students. Besides, the teacher gave materials which were familiar with the language used, understandable and interesting. It made the student enjoyed and followed the lesson well. It proved Murray and Christison (2011: 91) statement that the material accompanying the teaching learning process should be an appropriate level of difficulty of the learners, and relevant to the course syllabus. The second was the technique that the teacher used, that is Replacement Performance Role Play. The technique was applicable in the classroom. It was because the facilitation such as projector, LCD and speaker. Besides, the technique was deal with the procedure in the speaking proses as the teacher used three phases of speaking activity in teaching learning process. It helped the teacher to teach speaking affectively. As Nunan (2003) suggested that in speaking classroom, learners should be given the maximum number of opportunities possible to practice the target language in meaningful contexts and situation. For the students, this technique helped them to learn speaking easily. It was because this technique can encourage the students to participate more in speaking. The last was the teaching learning process. In implementing Replacement Performance Role Play to teach speaking, the teacher opened the class first, then, he used three phases speaking as a method in teaching (pre-speaking activities, whilst-speaking activities and post-speaking activities), then he ended the class. It is line with statement by Terry (2008: 5), that teaching stages for a speaking activity divided into three stages, they are pre-communicative stage (In pre-speaking activities), practice stage (In whilst-speaking activities) and communicative interaction or production stage. (In whilst-speaking activities and post-speaking activities). In opening stage, the teacher always greeted and took the students’ attendance list. He also gave brainstorming to the students in order to make the students’ fresh so that they were ready to follow the lesson. The teacher gave brainstorming at the last meeting only. He did not give brainstorming at the first and second meeting. Then, he also explained the objective of the lesson. He did it in each meeting. He told that they were going to use Replacement Performance Role Play. The students were enthusiastic and glad to hear that. In pre-speaking activities, the teacher began to stimulate the students by asking about the expression that they have known. Almost all of the students knew about the expression that they were going to learn. Then, the teacher added some addition expression. As stated by Diaz-Rico (2008: 226) that activate the background knowledge or make associations with similar situation are simple strategies in pre-speaking activity. After that, the teacher explained the material to the students clearly. In order to make the students understood about the lesson, the teacher gave an example of short dialogue and asked the students to find the expression. Then, he gave longer dialogue and practiced it with the students. However, the teacher did not give the longer dialogue at the second meeting. After that, the teacher divided the class into groups and each group consisted of four or five students. There are eight groups in each meeting. At the first meeting, the teacher faced difficulty in making groups because the students prefer to choose the member group by themselves. The teacher spent some minutes only to make groups. At the next meeting the teacher let the students to form a group themselves. It made the lesson run efficiently. Next, the teacher ordered the students to sit with their group to watch the video scene. The teacher gave different video in each meeting. The students watched the video scene quietly. In line with statement by Diaz-Rico (2008: 226) that there are some useful strategies in while speaking, they are monitor speech by paying attention to vocabulary, grammar, and pronunciation; try new words; back up and fix mistakes if necessary. In whilst-speaking activities, the teacher led the discussion about the story of the video which have already seen by the students. Some students followed the discussion well, while the rest students listened and paid attention in what their teacher and their classmates talked about. Sometimes, they gave a little addition. After the students knew about the story in the video, the teacher asked them to find the expression that they learned at that time. Then, the teacher shared a worksheet to each group and asked them to make a dialogue based on the video. The teacher explained that the dialogue did not have to be exactly same with the video. The students might use another word or another different expression. While the students were doing their task, the teacher walked around the class to monitor the students. The teacher helped the students to make a good dialogue. Before the representative of each group performed the dialogue in front of class, the teacher asked the groups to practice it with their friend in group. At the first meeting, only four groups performed the dialogue in front of class because the time was not enough. Moreover, at the second and third meeting, all representatives of each group performed their dialogue in front of the class. These are the following dialogue examples that made by the students. First Meeting Second Meeting Third Meeting In post activity, the teacher only gave comment or suggestion to students’ performance at the second and the third meeting. At least, the teacher closed the lesson by reviewing the material that they have been learned. It is also suggested by Diaz-Rico (2008: 226), that the teacher should evaluate accomplishment, reviewing goals and strategies, asking for feedback, and tuning in to the reactions of others in after speaking activity. We can see from the observation that the teacher prepared the lesson plan, the material and the technique well. He also always motivated the students to be active because it was speaking class. He used English as main language in the classroom. The teacher hoped from the students that they would participate more in speaking English through the implementation of Replacement Performance Role Play so that the goal of the teaching can be achieved. It proved with statement by Davies and Pearse (2000: 82) that the ability of speaking should be partly be the natural result of using English as the main means of communication in the classroom. Students’ Response toward the Implementation of Replacement Performance Role Play in Teaching Speaking Based on the result of questionnaire and interview, it was clear that the most of the students are interested in the teaching and learning speaking by the implementing of Replacement Performance Role Play. Snarski (2007: 3) pointed out that replacement performance role play can make the students engaged naturally. At the first, they felt that speaking English was difficult. They did not speak much at the English lesson because they were shy, afraid of making mistakes or did not know the material well. Although, they realized that learn to speak English is important for this globalization era. However, through the implementation of Replacement Performance Role Play, the students can practice and participate more in speaking. Most students said that they felt glad and enthusiastic when the teacher used Replacement Performance Role Play as a technique because they interested in this technique. As proved by Harmer (2007: 125) statement that role play stimulates the students in the real world in the same kind of way, but they are given particular roles. They felt that Replacement Performance Role Play help them in developing or expressing their idea easily. It also helped the students to speak English in appropriate way because the teacher gave some example dialogues and then practiced it with the students in good pronunciation. The teacher gave correction every time the students made mistakes. The video that was given by the teacher also helped the students how to speak English as native-like. It was because the cast in the video were native people. The students enjoyed to watch the video scene and discuss the story in the video together with the teacher. They also enjoyed work together with their friends in making dialogue. They had togetherness with the members of the group so that it motivated them to create a good dialogue. They can share their idea among the group’s member. All members in the group contributed in doing the task. They also tried to give best performance by practicing the dialogue together. CONCLUSION AND SUGGESTION Conclusion From the result of three meetings, it can be concluded that the implementation of Replacement Performance Role Play as a technique in teaching speaking for transactional and interpersonal to eleventh grade students of senior high school students can help the students to participate more in speaking English. In general, the implementation of Replacement Performance Role Play in teaching speaking was good. The teacher did the teaching learning process by three phase of speaking. Diaz-Rico (2008: 226) suggested to use three phase speaking process in teaching as a strategy to make the students participate more in speaking class. Most of the students were participated in each meeting because every student had same opportunities to develop their idea, expressing their idea and practicing their speaking skill. Even the shy students, they can practice their speaking in the small group through practicing the dialogue they have been made. It proved by Terry (2008: 3) statement that speaking exercise or speaking practice through conversation is most reliable technique that makes the student’ ability develops in communicative proficiency. The students’ respond toward the implementation of Replacement Performance Role Play was positive. They felt glad when the teacher used this technique. They said that Replacement Performance Role Play was interesting because they did not feel bored while teaching learning process. It was also helped the students to learn English easily. It proven with the statement by Snarski (2007: 3) stated that Replacement Performance Role Play provides valuable real-world practice (watch, discuss and practice) for language developments. They practiced to speak English in an appropriate way and in a good pronunciation. They enjoyed watching the video scene with native people as the character. Moreover, they enjoyed discussed the task together with their friend. They also enjoyed practicing the dialogue in a group. They thought that this technique is needed to be applied because it gave a lot of benefits not only for students in learning English easily and attractively but also for the teacher in making an effective, enjoyable and interesting teaching learning process. Suggestion Based on the result of the study, the researcher wanted to give some suggestion to the teachers who are interesting in implementing this technique and also for the other researchers who are attracting in doing a better research. For the English teacher a) Using the variety techniques, media or method in teaching learning process of a foreign language, such as: English, etc. is important. It will increase students’ interest, motivation, attention and participation in following the lesson that give by the teacher. Therefore, the teacher should be more creative in delivering the material to the students. Using a traditional method, technique or media allowed, but it is better to use the new one. It will make the students enjoy the material well and reduce their boredom. b) The teacher should choose proper materials which are suitable in students’ level. It should be based on Content Standard that has been established in curriculum. The vocabularies should be neither too easy nor too difficult. Besides, the materials should be attracting and interesting the students. It will lead to a successful learning. The goal of the teaching can be achieved by the teacher and the students can receive and understand the material well. c) The teacher should motivate the students to expressing their idea. Further, she or he should build the students’ confidence not shy to speak up. It will make the students not only learn the target language but also enhance their ability in all skill. For the other researchers This research investigated about the implementation of Replacement Performance Role Play as a technique in teaching speaking for transactional and interpersonal to eleventh grade students of senior high school students. For other researcher, they are expected to make better improvement. They can conduct a research in other fields concerning. They also can conduct a research in other subject such as: Replacement Performance Role Play as a technique in teaching speaking narrative, REFERENCES Ary, Donald, Jacobs, Lucy Cheser, Sorensen, Chris, & Razavieh, Asghar. (2001). Introduction to Research in Education. United States: Wadsworth cengage Learning.Brown, Douglas H. (2001). Priciples of language teaching and learning. New Jersey: Prentice Hall Inc. Diaz-Rico, Lynne T. (2008). A course for Teaching English Learners. United States: Pearson Education, Inc. Harmer, Jeremy. (2001). The Practice of English Language Teaching 3th ad. Malaysia: Pearson Education. Lindsay, Cora, & Knight, Paul. (2006). Learning and Teaching English : A Course for Teachers. New York: Oxford University Press. Murray, Denise E., & Christison, Mary Ann. (2011). What English Language Teachers Need to Know Volume II; Facilitating Learning. New York: Routledge. Norland, Deborah L., & Said, Terry Pruett. (2006). Teaching Adult ESL. Singapore: Mc Graw Hill. Nunan, David. (2003). Pratical English Language Teaching. New York: Mc Graw – Hills. Snarski, Maria. (2007). Using Replacement Performance RRole-Plays in the Language Classroom. English Teaching Forum, 4, 9. Terry, Carolina. (2008). How to Teach Speaking in an EFL Class. English Teaching Forum, 2(1).